Aproveitamento energético dos resíduos sólidos urbanos do futuro aterro sanitário sediado no município de Arapiraca/AL - Santana, Mayco Sullivan Araujo de (2016)
The uncontrolled emission of biogas, generated by solid waste, is a serious problem in the atmospheric atmosphere, both locally and globally and, consequently, its emission should be minimized. One way to minimize the impacts of biogas is not the environment through its reuse to generate electricity. The present research has as a proposal to carry out a survey of the energy potential of the solid waste from the future landfill of the region of the Alagoan agreste that is based in a city of Arapiraca, in order to evaluate its economic viability for electricity generation. For the development of the work done, in addition to revisions regarding the theme, field visits for data collection to characterize municipal solid waste municipal data collection gravimetric of the other constituent cities of the consortium for the last of the waste in the future Landfill No survey Of the energy potential was used the program LandGEM version 3.02 and from the data found for an economic analysis for its energy use. (48.4%), followed by flexible plastic (15.4%) and sanitary waste (10.4%). The gravity of the MSW of the municipality is constituted by 48.6%. (0.64%), wood (0.60%) and leather with (0.27%). The future landfill has a great energy potential reaching 46,237.70 kW over the life of the landfill, reaching 78,610.11 kW when considered a 20 year extension. As for the viability of using biogas to generate energy, the initial investment of R $ 19,732,965.00 and the time of return of the investment of 5 years and the NPV = R $ 4,276,405.58 without considering the carbon credit Return time of 4 years and NPV = R $ 6,835,326.15 if we consider the carbon credit, which makes the project feasible for two situations, being more attractive or investing with the commercialization of carbon credits. About 228,772 inhabitants were supplied with electricity during a life of the sanitary landfill and up to 388,943 inhabitants were built to generate energy for more than 20 years after the closure of the landfill.